The Relationship between Social Media Marketing Dimensions on Instagram and Increasing Patient Interest in Choosing a Hospital at Husada Hospital in 2025 - Suganda, Ernawati; Ellynia; Harahap, Sarah Geltri (LPPM Universitas Dhyana Pura, 2025)
In the increasingly digital era, the use of social media has become an important strategy in hospital marketing communications. Instagram, as a popular platform, is used by various hospitals to build a presence online and reach a wider audience. This study examines the influence of social media marketing dimensions through Instagram on patient decisions in choosing Husada Hospital as a healthcare provider, especially amidst the dynamics of post-pandemic visits and the digital transformation of hospital services. The purpose of this study was to determine the relationship between social media marketing dimensions on Instagram and patient decisions in choosing a hospital. This study used a quantitative approach with a cross-sectional study design involving 67 respondents. Data analysis was conducted univariately and used the Spearman test to examine the correlation between variables. The results showed a significant relationship between social media marketing dimensions and patient decisions. Husada Hospital has been actively using Instagram since 2018. Based on data, the number of followers in January-February reached 8,069 followers. And in March, followers increased to 8,161 followers. The social media marketing dimensions that most influence purchasing decisions are collaboration (r = 0.694), connection (r = 0.654), communication (r = 0.575), and context (r = 0.536). The most influential social media marketing dimension is collaboration. Active collaboration between Husada Hospital and influencers or medical personnel through Instagram has been proven to strengthen the hospital's image and encourage patient decisions. Therefore, it is recommended that Husada Hospital can further introduce and develop its official Instagram account @rs_husada strategically, through collaborative, educational, and interactive content to increase patient engagement and expand the hospital's digital marketing reach.